Professional communicative competence as a basic component of foreign language preparation of listeners - Khodjibaev, Ilhomjan (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The professional-communicative competence of students as the basic component of preparation of the Professional communicative competence of students is considered in the article as a basic component of preparation of highly skilled experts for interaction in the professional sphere